Al-Qur'an Learning Model in Improving The Quality of Students' Reading and Memorization At Daarul Mubarok Curup Islamic Boarding School (DMC) - filenti, elkin; Hendra Harmi; Irwan Fathurrochman (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study is based on the advantages of the DMC Islamic Boarding School, namely having students who memorize fluently with correct readings, prioritizing quality over quantity, having teachers with a sanad and referring to the international tahsin and tahfizh learning program whose sanad teachers continue to the Prophet Muhammad SAW. To analyze and find a model for learning tahsin and tahfizh Al-Qur'an in DMC Islamic Boarding School This study uses a qualitative research method with a case study approach . Informants are the head of the foundation, the head of the Islamic boarding school, the female tahsin and tahfizh teachers and students of DMC Islamic Boarding School . The technique of determining the informant is purposive sampling . The technique of collecting data is non-participant observation, interviews and documentation. The results of the study are the tahsin and tahfizh learning model at DMC Islamic Boarding School, including syntax; prioritizing muraja'ah then submitting new memorization, social system; teaching, listening, and guiding with patience and tolerance by not setting a minimum target for the number of memorizations. Reaction principle; the teacher teaches, then the students follow together. Supporting system; approach; theological and psychological, tilawati method and having teachers who are related. Tahsin and tahfizh learning model The Qur'an at the DMC Islamic Boarding School is a Mutqin model.